Assessing the impact of minimizing arginine conversion in fully defined SILAC culture medium in human embryonic stem cells. Issue 20 (12th September 2016) - Scheerlinck, Ellen; Van Steendam, Katleen; Daled, Simon; Govaert, Elisabeth; Vossaert, Liesbeth; Meert, Paulien; Van Nieuwerburgh, Filip; Van Soom, Ann; Peelman, Luc; De Sutter, Petra; Heindryckx, Björn; Dhaenens, Maarten; et al.
Abstract : We present a fully defined culture system (adapted Essential8 TM [E8 TM ] medium in combination with vitronectin) for human embryonic stem cells that can be used for SILAC purposes. Although a complete incorporation of the labels was observed after 4 days in culture, over 90% of precursors showed at least 10% conversion. To reduce this arginine conversion, E8 TM medium was modified by adding (1)l ‐proline, (2)l ‐ornithine, (3) N ω ‐hydroxy‐nor‐l ‐arginine acetate, or by (4) lowering the arginine concentration. Reduction of arginine conversion was best obtained by adding 5 mMl ‐ornithine, followed by 3.5 mMl ‐proline and by lowering the arginine concentration in the medium to 99.5 μM. No major changes in pluripotency and cell amount could be observed for the adapted E8 TM media with ornithine and proline. However, our subsequent ion mobility assisted data‐independent acquisition (high‐definition MS) proteome analysis cautions for ongoing changes in the proteome when aiming at longer term suppression of arginine conversion.